THE EFFECT OF PRENATAL MASSAGE ON BACK PAIN IN PREGNANT WOMEN IN THE THIRTY TRIMESTER IN INDEPENDENT MIDWIFE PRACTICE (PMB) SITI AISAH, PAGAR DEWA DISTRICT WEST LAMPUNG DISTRICT - Wardani, Psiari Kusuma; Apriani, Heni Teresia; riani, Yunita Angg; Devi, Inggit Prima; Kustanti, Nindy Retno (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2025)
This study aims to determine the effect of prenatal massage on back pain in pregnant women in the third trimester at the Siti Aisah Independent Midwife Practice (PMB), Pagar Dewa District, West Lampung Regency in 2024. This study was motivated by the high prevalence of pregnant women experiencing low back pain (LBP) in Pagar Dewa District, which is estimated to reach 65%. Management to reduce lower back pain can be done with prenatal massage, which is a massage specifically designed for pregnant women to improve blood circulation and reduce complaints that are often experienced by pregnant women. The research method used was a pre-experimental design with a one group pretest posttest approach. The study population consisted of 34 pregnant women in the third trimester at PMB Siti Aisah, with a sample of 18 respondents selected using the purposive sampling technique. Data were collected through observation sheets and analyzed using univariate and bivariate statistical tests (Wilcoxon test). The results showed that the average level of back pain in pregnant women before the intervention was 5.3, and after being given intervention with prenatal massage decreased to 2.8 with a decrease of 2.5 (p-value = 0.000). Based on these results, it is recommended that midwives can apply prenatal massage in their practice to provide non-pharmacological therapy in overcoming back pain in pregnant women.